2014
DOI: 10.1159/000364876
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Assessment of Renal Size in Healthy Adults

Abstract: Objective: To assess the normal sonographic values of renal length and cortical thickness in healthy adults and establish reference ranges in our population for comparison when examining renal disease. Subjects and Methods: Sonographic assessment of renal length and cortical thickness were performed from January 2006 to December 2011 in 252 healthy individuals who were self-referred to the El-Reshaid Renal Clinic in Kuwait. They were screened for the absence of renal abnormalities. Weight and height were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
67
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 20 publications
4
67
2
2
Order By: Relevance
“…A normal range of 8 to 11.5 mm was reported in a small study of transplant donors by Raj et al 15 However, ElReshaid et al stated that cortical thickness values up to 6 mm are also considered to be normal. 16 The mean cortical thickness in our study was found to be 8.5 mm (Range 5.2 mm -12.8 mm; SD=1.63 mm). Cortical thickness could not be assessed in 16 patients as the renal pyramids could not be identified on USG.…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…A normal range of 8 to 11.5 mm was reported in a small study of transplant donors by Raj et al 15 However, ElReshaid et al stated that cortical thickness values up to 6 mm are also considered to be normal. 16 The mean cortical thickness in our study was found to be 8.5 mm (Range 5.2 mm -12.8 mm; SD=1.63 mm). Cortical thickness could not be assessed in 16 patients as the renal pyramids could not be identified on USG.…”
Section: Discussionmentioning
confidence: 40%
“…10 The renal length has also been showed to vary with weight and BMI of the person. 16 Although ischaemic nephropathy causes cortical thinning, renal hypertrophy in diabetic nephropathy affects all components, so that the kidney maintains its shape and architecture in the early phase. Due to the incipient nephromegaly, the diabetic kidney often looks bigger and 'Better' than the kidney with the same level of chronic, irreversible renal failure caused by other chronic renal diseases such as other glomerular diseases, hypertensive nephropathy or tubulointerstitial diseases.…”
Section: Discussionmentioning
confidence: 99%
“…They explained it on the basis of rapid body growth that occurring before the attainment of mature body morphology at adult stage [29]. El-Reshaid et al [30] estimated sonographic values of renal dimensions in 252 patient aged 18-80 yrs. without any renal disease in Kuwait.…”
Section: Bmi Influencing Renal Lengthmentioning
confidence: 99%
“…Pearson correlation test also showed that renal length increased by 0.23 cm for each 10 kg increase in body weight within the range of 60-120 kg. The explanation given by the authors was that larger body size requires a larger nephron dose to meet its metabolic demands [30].…”
Section: Bmi Influencing Renal Lengthmentioning
confidence: 99%
“…Other studies done in Kuwait, Denmark, and Austria have assessed renal volumes in their population by either ultrasound or computed tomography and have helped establish a baseline of renal volume for their countries. [21][22][23][24] Differences in body build and body composition between different ethnic groups suggest that creatinine-based estimated GFR (eGFR) derived for European populations may not be appropriate for others as muscle mass is a key determinant of serum creatinine levels and hence eGFR. 25 Healthy Indians have lower muscle mass in comparison to Africans and Caucasians and hence a lower serum creatinine.…”
mentioning
confidence: 99%